Mauli banana stem extract application increased expression of NF-κB in traumatic ulcer healing - Maharani Laillyza Apriasari; Retno Pudji Rahayu; Diah Savitri Ernawati (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2018)
Background: A traumatic ulcer represents one of the most prevalent disorders affecting the oral cavity. Ulceration of the oral cavity potentially results in secondary infection requiring topical medication which involves the use of antiseptics to accelerate wound healing. Previous research has shown that Mauli banana (Musa acuminata) stem extract (MBSE) contains bioactive material from terpenoid saponin present in Ambon bananas. The terpenoid saponin in Ambon banana stems will be captured by a G protein receptor in the macrophages, subsequently producing a protein kinase C that activates nuclear factor kappa beta (NF-κB). This increases both the activity and number of macrophages. Purpose: To analyze the expression of NF-κB (p50) in traumatic ulcers as an effect of MBSE. Methods: A true experimental design with a post-test only control group. It involved 40 male Rattus norvegicus strain rats as traumatic ulcer models divided into four groups: the negative control group administered gel, and the other treatment groups administered 25%, 37.5% and 50% ethanol extracts of MBSE gel respectively. A biopsy was performed on days 3 and 5. The preparation was produced to analyze the expression of NF-κB (p50) by means of immunohistochemistry examination. Results: There was a significant difference (p<0.05) in NF-κB (p50) expression (p=0.005) following MBSE gel administration of 37.5% concentration on day 3 compared to day 5. Conclusion: It can be concluded that MBSE gel topical application can increase expression of NF-κB (p50) in traumatic ulcer healing.